Is it time to screen for the Haptoglobin genotype to assess the cardiovascular risk profile and vitamin E therapy responsiveness in patients with diabetes? - Vardi, Moshe (2012)
Diabetes mellitus (DM) carries an increased risk for cardiovascular complications. Haptoglobin (Hp) is an abundant plasma protein with an anti-oxidant function by virtue of its ability to block the oxidative activity of extracorposcular hemoglobin. There exist two common functional alleles at the Hp genetic locus, denoted 1 and 2, with three Hp genotypes (Hp 1-1, 2-1 and 2-2). The Hp protein expressed in Hp 2-2 individuals is markedly inferior in protecting against hemoglobin induced oxidative stress. Hp 2-2 DM individuals have been shown to be at increased risk for the development of diabetes complications, particularly diabetic cardiovascular disease (CVD). We review here the biological mechanisms underlying the interaction between the Hp genotype and DM on CVD and the accumulating evidence in favor of Hp genotyping all individuals with DM and providing antioxidant vitamin E supplementation specifically to Hp 2-2 DM individuals in order to reduce their CVD morbidity and mortality.